Health benefits of Kombucha: drink and its biocellulose production - Luis Otávio Aguiar Cavicchia; Martha Elisa Ferreira de Almeida (Universidade de São Paulo, 2023)
Abstract Kombucha (tea and biocelluose) has been used worldwide due to its high nutritional, functional, and economic potential. This fermented tea has been used in folk medicine to treat several pathological conditions and its biocellulose in the industrial sector. In this context, this paper presents a scientific literature review on the main phytochemicals of Kombucha and respective biological activities to assess their potential uses. The tea has presented a wide range of bioactive compounds such as amino acids, anions, flavonoids, minerals, polyphenols, vitamins, and microorganisms. Moreover, its biocellulose is rich in fibers. These compounds contribute to various biological responses such as antioxidant, hepatoprotective, antitumoral, antidiabetic, and antihypercholesterolemic effects. In this sense, both the tea and its biocellulose are promising for human use. Besides, Kombucha presents itself as a drink option for vegetarians and/or those seeking healthier diets, as its biocellulose can bring metabolic benefits. Our review demonstrates that both can be used as functional foods and/or sources of bioactive compounds for food and industrial applications.